Democracy and the Religious Paradox:The Impact of Polit-ical Change on Islamic Identity in Muslim-Majority Coun-tries (Lembaga Pengembangan Kinerja Dosen, 2025)
This study explores the paradox of democracy in Muslim-majority societies, particularly how democratic political systems influence the role of religion and the construction of religious identity. Employing a qualitative-descriptive approach through literature review and case studies in Indonesia and Turkey, this article finds that democracy opens participatory space for religious expression while simultaneously enabling the domination of majoritarian Islamic identity in the public sphere. This transformation leads to the fragmentation and commodification of religious identity, shifting it from a spiritual-transcendent value toward a symbolic-political function. In Indonesia, post-Reformasi democracy has fostered the expansion of conservative Islamic movements via electoral and social mobilization. In Turkey, democratization under the AKP regime has turned into religious populism that undermines secularism. The study concludes that democracy in Muslim-majority societies holds a paradoxical potential: it can serve as a medium for religious reform or become a tool for identity-based hegemony. Hence, strengthening institutions, political ethics, and reflective religious narratives is essential to make democracy a just and inclusive arena.